2013
DOI: 10.1002/chem.201303693
|View full text |Cite
|
Sign up to set email alerts
|

Tetrafluorination of Sugars as Strategy for Enhancing Protein–Carbohydrate Affinity: Application to UDP‐Galp Mutase Inhibition

Abstract: Tetrafluorinated analogues of both UDP-galactopyranose and UDP-galactofuranose have been synthesized and assayed against UDP-galactopyranose mutase, a key enzyme for Mycobacterium tuberculosis cell wall biosynthesis. Competition assays and STD-NMR spectroscopy techniques have evidenced not only the first unambiguous case of affinity enhancement through local sugar polyfluorination, but also showed that tetrafluorination can still have a beneficial effect on binding when monofluorination at the same position do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…N'Go et al 37 have reported that UDP-F 4 -Galf 4 adopts a high energy conformation ( 4 E) in its MtUGM-bound state, as evidenced by a H1-H4 nOe crosspeak obtained by a TRNOESY experiment, as opposed to the minimum energy conformation adopted in the free state ( 3 T 2 ). This in solution NMR-based observation is now confirmed by the X-ray crystallographic data obtained in this study.…”
Section: Mtugm:udp-f 4 -Galf Complex Structurementioning
confidence: 99%
“…N'Go et al 37 have reported that UDP-F 4 -Galf 4 adopts a high energy conformation ( 4 E) in its MtUGM-bound state, as evidenced by a H1-H4 nOe crosspeak obtained by a TRNOESY experiment, as opposed to the minimum energy conformation adopted in the free state ( 3 T 2 ). This in solution NMR-based observation is now confirmed by the X-ray crystallographic data obtained in this study.…”
Section: Mtugm:udp-f 4 -Galf Complex Structurementioning
confidence: 99%
“…[13] A successful inhibitor of the mycobacterial enzyme UDP-Gal mutase, based on a tetrafluorinated galactofuranose sugar, has been recently reported. [14] Figure 1. Tetrafluorinated sugars with the proposed aminosugar analogues.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the UGM inhibitors developed to date have only moderate binding affinities in the micromolar range, [9][10][11][12][13][14][15][16][17][18] unsuitable for clinical application. Hence, understanding their bound geometries could be critical to improving the potency of UGM inhibitors.…”
mentioning
confidence: 98%
“…One such micromolar inhibitor, UDP-(2,3-dideoxy)-2,2,3,3-tetrafluoro-D-galactofuranose (UDP-F4-Galf) (Scheme 1), has been recently developed and shows a K d of 53 lM against the model UGM enzyme from Klebsiella pneumoniae. 18 In addition, its binding epitope in complex with UGM has been mapped by saturation transfer difference (STD) NMR spectroscopy. 18 To reveal the bioactive bound conformation of this tetrafluorinated substrate analogue within the active site, we employ herein molecular dynamics (MD) simulations to construct its binding model with reduced (catalytically active) UGM.…”
mentioning
confidence: 99%
See 1 more Smart Citation